Is Crime Bad for Your Health? The Link Between Delinquent Offending and Cardiometabolic Risk - Schwartz, Joseph A. (Crime & delinquency, 2020)
Specific sources of psychophysiological dysfunction have been identified as a primary mechanism of the association between stress and health, wherein chronic and prolonged exposure to stressors results in downstream negative consequences of stress-linked dysregulation that increase the likelihood of chronic health problems. Factors pertinent to criminological inquiry have been previously identified as sources of physiological dysfunction, but the extent to which offending over the life course operates in a similar manner has yet to be examined. The current study examines the longitudinal association between delinquency and physiological dysfunction in cardiovascular and metabolic functioning (i.e., cardiometabolic risk). The results of longitudinal structural equation models revealed that greater levels of delinquency are associated with higher levels of cardiometabolic risk.